Odpowiedzi

2009-12-08T19:55:26+01:00
X-3y=5
y+3x=-5

x-3y=5
3x+y=-5 /*3

x-3y=5
9x+3y=-15
-------------- dodajemy
10x=-10
x=-1

3x+y=-5
y=-5-3x
y=-5+3
y=-2
2009-12-08T19:57:02+01:00
X-3y=5
y+3x=-5

x-3y=5
3x+y=-5 /*3

x-3y=5
9x+3y=-15

10x=-10 /podzielić przez 10

x=-1

x=-1
y+3x=-5

x=-1
y+3(-1)=-5

x=-1
y=-5+3

x=-1
y=-2
2009-12-08T19:58:35+01:00
X-3y=5
y+3x=-5 - mnożymy przez 3
x - 3y = 5
3y + 9x = -15
x - 3y + 3y + 9x = 5 - 15
x + 9x = - 10
10x = - 10
x = - 1
x - 3y= 5
- 1 - 3y = 5
- 3y = 5 + 1
- 3y = 6
y = - 2
x = - 1